Two new species of Platanthera (Orchidaceae, Orchidoideae) from Xizang, China - Lin, Dongliang; Zhang, Liyue; Ye, Chao; Li, Jianwu; Jin, Xiaohua (Phytotaxa, 2024)
Two new orchid species, Platanthera linzhiensis, P. deergongensis, are described and illustrated from Motuo, Xizang, China. P. linzhiensis is closely related to P. uniformis, but differs from it by lip yellowish green, spur yellow, nearly as long as ovary, connective obtuse-truncate, not protruding from anther, column lateral appendages ovate to oblong, slightly shorter than the anther. P. deergongensis is morphologically similar to P. contigua, but is distinguished from it by having white lip, obtuse-truncate connective and ovate to oblong column lateral appendages. Molecular phylogenetic analysis based on six markers (nrITS, psaB, matK, psbA-trnH, rbcL, trnL-F) revealed that P. linzhiensis and P. deergongensis formed a clade with high support, and are close to P. superantha.